Vom Berliner Schloss zum Humboldt Forum: ein Paradigma Deutscher Konfliktgeschichte - Bredekamp, Horst (Artium Quaestiones, 2019)
The lecture concerns the Berlin Palace (Stadtschloss) and presents a view of its long history, starting with its construction in the Baroque style by an artist of the Polish origin, Andreas Schlüter, up to its contemporary reconstruction with a new institutional function (Humboldt Forum). The ten sections of the text not only present architectural and artistic history of this residence but also pivotal historical events and contexts which affected the dimensions and meaning of its functioning. The Palace, entangled into German history but also reflecting it, especially as regards the 19th and 20th centuries, becomes both a starting point for an evaluation of this history and posing questions about the future. Along with the ferociously debated, present-day reconstruction and its museum function, it also seems to be a psychogram of diverse stages of the condition of German spirit.